EFFICACY AND SAFETY OF TENELIGLIPTIN AS ADD-ON THERAPY TO CONVENTIONAL THERAPY IN INDIAN PATIENTS WITH TYPE 2 DIABETES MELLITUS - PARMAR VINENDRA M; GOSWAMI SUNITA S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Teneligliptin is a novel, highly selective dipeptidyl peptidase-4 inhibitor. The objective of the present study was to investigate the efficacy and safety of teneligliptin as add-on therapy in patients with type 2 diabetes mellitus (T2DM) who are inadequately controlled by conventional therapy (metformin/glimepiride) in India. Methods: Clinical study protocol was approved by the Institutional Ethics Committee. T2DM patients (male/female) whose glycated hemoglobin (HbA1c) >7% were randomized to receive following group treatments, namely, Treatment A: Metformin/glimepiride plus add-on teneligliptin 20 mg and Treatment B: Metformin/glimepiride for 24 weeks. A pre-designed case report form was used to collect information from the prescribing physicians regarding the efficacy and safety of teneligliptin. Efficacy variables included change in plasma blood glucose (fasting and postprandial) and HbA1c from baseline to week 24. Treatment emergent adverse events were assessed. Results: A total of 120 type 2 diabetes patients were analyzed. Teneligliptin as add-on therapy with metformin/glimepiride significantly reduced plasma glucose (HbA1c, fasting, and postprandial) concentration as compared to conventional therapy. Conclusion: Add-on therapy with teneligliptin was found superior over conventional therapy in reducing plasma glucose concentration (fasting and postprandial) and HbA1c levels significantly in patients with T2DM. Further, it was found effective and well tolerated in Indian patients with T2DM who are inadequately controlled with conventional therapy.